Effect of orthodontic forces on root length of immature mandibular second premolars: a split-mouth randomized clinical trial - Kazem DALAIE; Mohammadreza BADIEE; Mohammad BEHNAZ; Shahab KAVOUSINEJAD (Dental Press Editora, 2021)
ABSTRACT Objective: To assess the effect of orthodontic forces on changes in root length of immature mandibular second premolars. Methods: Sixty-four mandibular second premolars (MSP) with immature apices (left and right sides) of 32 patients aged between 10 and 13 years were evaluated. Orthodontic treatment was started after obtaining periapical radiographs (T1) from the MSPs of each patient. Brackets were bonded, except the ones of MSPs (left or right by random as control MSP, and the other side as test MSP). After 9-12 months, a second periapical radiograph (T2) was obtained from the MSPs of each patient. Then, brackets were bonded to the control MSPs, which were not bonded before. After 18 ± 3 months, a third periapical radiograph (T3) was obtained. Changes in root length were evaluated by using a new formula. The test and control MSPs at T1, T2 and T3 were compared using repeated measures ANOVA and parametric tests. P-value smaller than 0.05 was statistically significant. Results: There was no significant difference between the test and control groups in the mean root length of MSP at T1 (p= 0.48) and T3 (p= 0.078). The root length at T2 (p= 0.001) was significantly different between test and control MSPs, and the test group showed longer root length than the control group. Conclusions: Orthodontic force applied for leveling and alignment of immature MSPs may not have destructive effects on the roots, and may accelerates root formation in short-term. Normal root length was achieved at the end of root development.